Lupus and recurrent pregnancy loss: the role of female sex hormones and B cells - Valeff, Natalin Jimena; Ventimiglia, Maria Silvia; Diao, Lianghui; Jensen, Federico (Frontiers in Endocrinology, 2023)
Systemic Lupus erythematosus is a debilitating autoimmune disease characterized by uncontrolled activation of adaptive immunity, particularly B cells, which predominantly affects women in a 9 to 1 ratio compared to men. This stark gender disparity strongly suggests a role for female sex hormones in the disease's onset and progression. Indeed, it is widely recognized that estradiol not only enhances the survival of autoreactive B cells but also stimulates the production of autoantibodies associated with systemic lupus erythematosus, such as anti-nuclear antibodies and anti-dsDNA antibodies, among others. Clinical manifestations of systemic lupus erythematosus typically emerge after puberty and persist throughout reproductive life. Furthermore, symptoms often exacerbate during the premenstrual period and pregnancy, as increased levels of estradiol can contribute to disease flares. Despite being fertile, women with lupus face a heightened risk of pregnancy-related complications, including pregnancy loss and stillbirth, which significantly surpass the rates observed in the healthy population.Therefore, this review aims to summarize and discuss the existing literature on the influence of female sex hormones on B-cell activation in systemic lupus erythematosus patients, with a particular emphasis on their impact on pregnancy loss.